อาหารอย่างง่ายสำหรับการเพาะเลี้ยงโปรโตคอร์มกล้วยไม้เอื้องพร้าว - นารถกาญจน์ ลภิรัตนากูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purpose of this reseach was to study the simple culture media for Phaiustaius tankerilleae protocorm and to produce an instruction media of plant tissue culture for classroom. Phaiustaius tankerilleae's seeds were cultured on the VW (Vacin and Went) media for 4 weeks until the protocorms were developed. The protocorms were transferred to four simple culture media: OD (Oradee Sahavacharin), TisTR (Thailand Institube of Scientific and Technological Research), NK (Nattakan), and VW and incubated for 7 weeks. The results showed that the mean diameter of the protocorms were insiginficantly different (p<0.05). Moreover, the shoots were induced their at 100 % with these four media. The best results were obtained using VW and NK formula only could be measured that the average length of shoots were 18.00 and 17.08 mm respectively which were insiginficantly different (p<0.05).